Penerapan Metode Diskusi dalam Memahami Materi Rukhsah pada Mata Pelajaran PAI - Raito Raito; Dewi Nursaadah (STAI Al-Musaddadiyah Garut, 2026)
One of the problems facing the world of education today is the weakness of the learning process. During the learning process, students are not encouraged to develop their thinking skills. The learning process in the classroom is directed at children's ability to memorize information. Children's brains are forced to remember and accumulate various information and are required to understand the information they remember and relate it to everyday life. The impact is that when students have completed their studies, they are skilled in theory, but poor in application. The strategies or methods used by educators in teaching Islamic Religious Education are very effective for improving Islamic Religious Education learning. One approach that is considered effective is the discussion method. The purpose of this study is to describe the process of applying the discussion method to understand the rukhsah material in Islamic Religious Education (PAI) subjects using the Merdeka curriculum approach. This study uses a descriptive qualitative method to determine the application of the discussion method in understanding the material of rukshsah. Therefore, this study focuses on the application of the discussion method in understanding the material of rukshsah in Islamic Religious Education (PAI). The results of the study on the application of the discussion method in the PAI subject of Rukshsah. The application of the discussion method effectively increases students' understanding of the concept of rukshsah in worship. Through discussions, students can exchange ideas, express opinions and explore concrete examples of forms of rukshsah such as relief in prayer, fasting, salary and so on according to certain conditions.Keywords: Discussion Method, Islamic Education Subject